2014
DOI: 10.1021/ja5102823
|View full text |Cite
|
Sign up to set email alerts
|

Trapped State Sensitive Kinetics in LaTiO2N Solid Photocatalyst with and without Cocatalyst Loading

Abstract: In addition to the process of photogeneration of electrons and holes in photocatalyst materials, the competitive process of trapping of these charge carriers by existing defects, which can both enhance the photocatalytic activity by promoting electron-hole separation or can deteriorate the activity by serving as recombination centers, is also very crucial to the overall performance of the photocatalyst. In this work, using femtosecond diffuse reflectance spectroscopy we have provided evidence for the existence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 38 publications
3
47
1
Order By: Relevance
“…In fact, it was recently suggested that the charge migration distance in LTC was on the order of microns in the case of LTC/Au photocathodes, because PEC deposition of noble metal nanoparticles occurred only onto the tip of rod-like LTC particles a few micrometres in length. 9 In order to further investigate the nature of photogenerated charge carriers in LTC powder, we employed transient absorption spectroscopy (TAS), which has been successfully used in monitoring carrier dynamics in many semiconductor photocatalysts 21,22 (see ESI† for experimental details). Since the powder was opaque, we collected and analyzed the diffuse reflected light from the sample, instead of transmitted light, to obtain information on the kinetics of transient species; femtosecond time resolved diffuse reflectance (fs-TRDR) spectroscopy was employed.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it was recently suggested that the charge migration distance in LTC was on the order of microns in the case of LTC/Au photocathodes, because PEC deposition of noble metal nanoparticles occurred only onto the tip of rod-like LTC particles a few micrometres in length. 9 In order to further investigate the nature of photogenerated charge carriers in LTC powder, we employed transient absorption spectroscopy (TAS), which has been successfully used in monitoring carrier dynamics in many semiconductor photocatalysts 21,22 (see ESI† for experimental details). Since the powder was opaque, we collected and analyzed the diffuse reflected light from the sample, instead of transmitted light, to obtain information on the kinetics of transient species; femtosecond time resolved diffuse reflectance (fs-TRDR) spectroscopy was employed.…”
Section: Discussionmentioning
confidence: 99%
“…In the effort to develop photocatalysts based on TiO 2 , a large number of recent researches have been devoted to investigation of integrated composite TiO 2 catalysts [12][13][14][15][16][17][18][19][20][21]. For example, transition metal doping TiO 2 is effective to improve the Page 6 of 27 A c c e p t e d M a n u s c r i p t photocatalytic activity by decreasing the charge carrier recombination rates [12,13]; and other various non-metal-doped TiO 2 have been widely studied for the visible light photocatalytic activities [11,15,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to classical bulk heterojunction, the full surface of CN should not be covered by the cocatalyst because the hole (which remains inside the CN after the dissociation) must react with the hole scavenger at the interface between CN and the electrolyte. The presence of this silica might help scavenge the surface holes 75 and thereby, surface electrons can have time to go to the Pt active site, precluding the loss due to electron-hole recombination, which is prevalent in bare CN. Thus, the competitive process of trapping the charge carrier, particularly the hole, by the existing defects in the silica in a way hinders the recombination loss and enhances the photocatalytic activity by promoting electron-hole separation.…”
mentioning
confidence: 99%